Performance study of plant based coagulant to treat electroplating wastewater: article - Kamaludin, Ariena Shazwani; Md Som, Ayub (2017)
The performance of dragon fruit foliage as a natural coagulant for treatment of electroplating wastewater was investigated by the jar test. The study also compared different dosages and pH values to determine the effectiveness of coagulation process. Dragon fruit foliage comes from the family Cactaceae which possess natural characteristics of the alum. Electroplating wastewater is one of the industrial effluents that contain high organic and inorganic substances as well as heavy metals that are harmful to the environment. Three main parameters; chemical oxygen demand (COD), suspended solid (SS) and Turbidity of wastewater were investigated in this study. From the experiment, the optimum percentage removals recorded for COD, SS and Turbidity were observed for effluent pH 10 and fixed dosage of 200 mg/L, at 89.6%, 76.9% and 89.7 % respectively. It is concluded that dragon fruit foliage works extremely efficient as natural coagulant to treat electroplating wastewater.